Water and Sanitation as Human Rights: Have They Strengthened Marginalized Peoples’ Claim for Access? - Wilson, Bruce M.; Brinks, Daniel; Singh, Arkaja (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book investigates the impact of the United Nations General Assembly's 2010 resolution that elevated rights to water and sanitation are stand-alone international human rights. A major goal of creating this new human right was to incentivize governments to prioritize and pursue policies to improve access to affordable, potable water to the more than 750 million people worldwide who lacked access, as well as to provide the more than 2.5 billion people with inadequate sanitation. The book's chapters use a variety of methodological approaches including qualitative case studies and quantitative studies that draw on data from around the world. The chapters reveal how the global human right to water and sanitation was created, how it has been used in rights struggles around the world, and the extent to which it has improved access to water and sanitation for the world's most marginalized people.